Comparative Analysis of Dorsal Root, Nodose and Sympathetic Ganglia for the Development of New Analgesics - Sapio, Matthew R.; Vazquez, Fernando A.; Loydpierson, Amelia J.; Maric, Dragan; Kim, Jenny J.; LaPaglia, Danielle M.; Puhl, Henry L.; Lu, Van B.; Ikeda, Stephen R.; Mannes, Andrew J.; Iadarola, Michael J. (Frontiers in Neuroscience, 2020)
Interoceptive and exteroceptive signals, and the corresponding coordinated control of internal organs and sensory functions, including pain, are received and orchestrated by multiple neurons within the peripheral, central and autonomic nervous systems. A central aim of the present report is to obtain a molecularly informed basis for analgesic drug development aimed at peripheral rather than central targets. We compare three key peripheral ganglia: nodose, sympathetic (superior cervical), and dorsal root ganglia in the rat, and focus on their molecular composition using next-gen RNA-Seq, as well as their neuroanatomy using immunocytochemistry and in situ hybridization. We obtained quantitative and anatomical assessments of transmitters, receptors, enzymes and signaling pathways mediating ganglion-specific functions. Distinct ganglionic patterns of expression were observed spanning ion channels, neurotransmitters, neuropeptides, G-protein coupled receptors (GPCRs), transporters, and biosynthetic enzymes. The relationship between ganglionic transcript levels and the corresponding protein was examined using immunohistochemistry for select, highly expressed, ganglion-specific genes. Transcriptomic analyses of spinal dorsal horn and intermediolateral cell column (IML), which form the termination of primary afferent neurons and the origin of preganglionic innervation to the SCG, respectively, disclosed pre- and post-ganglionic molecular-level circuits. These multimodal investigations provide insight into autonomic regulation, nodose transcripts related to pain and satiety, and DRG-spinal cord and IML-SCG communication. Multiple neurobiological and pharmacological contexts can be addressed, such as discriminating drug targets and predicting potential side effects, in analgesic drug development efforts directed at the peripheral nervous system.